ANALISIS PERGESERAN SEKTOR PERTANIAN DI KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Rahmanta Ginting (Quantitative Economics Journal, 2014)
Principally the sectoral shift and development in a region is a sustainable activityto realize a good condition collectively and continuously. The objective of thisresearch is to analyze the change and shift of agricultural sector to the localeconomic condition in Regency of Langkat. The data applied in this research issecondary data collected from any institution/organization related to the studiedproblem since 2007 up to 2012. The applied data analysis method is Shift Share Analysis. This method is applied to observe the economic structure and its shift by focus to sectoral development in region than the same one in the higher regional level or in national level. The results of research indicates that (a) agricultural sector is a sector with the bigger role in the Gross Regional Domestic Product (GRDP) of Langkat regency, (b) the national share value for agricultural sector and industry with a rapid growth than the other sectors, (c) the value of differential shift, agricultural sector, industry, electricity and gas, building, transportation and financial is a sector with higher competitive or sector with the rapid shift growth than other sector, and (d) the results of shift share analysis indicates that there is development of GRDP for 93.50 percent.